2021
DOI: 10.1002/jppr.1728
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Beers criteria and potentially inappropriate medications among physicians and pharmacists in Palestine

Abstract: Background: The American Geriatric Society Beers criteria comprise a screening tool to identify potentially inappropriate medications (PIMs) and guide healthcare providers (HCPs) in prescribing, dispensing, and recommending appropriate medications. The extent of awareness about PIMs and geriatric medicine among HCPs needs to be assessed. Therefore, this study aimed to examine the level of awareness regarding PIMs and Beers criteria among HCPs in Palestine. Method: This was a cross-sectional study conducted usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
(31 reference statements)
1
6
0
Order By: Relevance
“…Despite having poor knowledge and awareness about PIM screening tools, respondents showed a high degree of self-confidence in detecting PIMs in older adults. Our findings align with a similar study from Palestine, which showed that 34% of their participants had poor awareness of the PIM tool [ 38 ]. Surprisingly, half the participants were confident enough to identify PIMs by utilising the appropriate medication references.…”
Section: Discussionsupporting
confidence: 92%
“…Despite having poor knowledge and awareness about PIM screening tools, respondents showed a high degree of self-confidence in detecting PIMs in older adults. Our findings align with a similar study from Palestine, which showed that 34% of their participants had poor awareness of the PIM tool [ 38 ]. Surprisingly, half the participants were confident enough to identify PIMs by utilising the appropriate medication references.…”
Section: Discussionsupporting
confidence: 92%
“…18 Therefore, educating and training geriatric health care providers and recruiting clinical pharmacists in hospitals will play a vital role in improving health care outcomes and reducing PIPs. 1 The use of multiple medications to treat chronic diseases, severe illnesses, and other health problems, known as polypharmacy, is more common among elderly patients because they have experienced multiple comorbidities and chronic and acute diseases that need to be treated by a variety of drugs. 20 Moreover, multiple medications increase drugdrug and drug-disease interactions, which may cause serious adverse events, especially among geriatric patients.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Therefore, educating and training geriatric health care providers and recruiting clinical pharmacists in hospitals will play a vital role in improving health care outcomes and reducing PIPs. 1 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations